EFFECT OF KAOLIN ON HEMATOLOGICAL AND BIOCHEMICAL PARAMETERS OF CYPRINUS CARPIO L. AGAINST COPPER SULFATE TOXICITY - Mutaz S. Al-Tamimi; A. J. Al-Rudainy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The present study was aimed to evaluate the effect of kaolin on copper sulfate toxicity and on some hematological and biochemical performance in Cyprinus carpio L. 240 common carp ranged between 85-95g in weight. A total of 120 fish were used to determine the median lethal concentration LC50 of copper sulfate and 120 fish and randomly distributed into six treatments (two replications for each treatment). The LC50 of copper sulfate was 1.82 mg/l for 48h exposure, then added 0.91mg/l of copper sulfate to all treatment groups except control negative .The experimental treatments included adding kaolin: Control negative (without copper sulfate or kaolin); Control positive 0.91mg/l copper sulfate without kaolin.T1, T2, T3 and T4 kaolin were added in the water at levels of 2, 4 , 6 and 8 g/l respectively. Results showed that the values of RBCs count were ranged 1.16 x106 - 1.77x106 cell /mm³ in cont.+ve and T3 respectively. WBCs count were ranged 8.40×10³ in cont.+ve to 13.14×10³ cell/mm³ in T3.The lowest Hb content found in cont.+ve reached 8.35 g/dl, while the highest content found in control-ve attained 12.87g/dl. PCV ranged from 21.75 to 35.60% in cont.+ve and T3 respectively. Results of total protein ranged between 6.6 - 18.19 g/dl in T4 and cont.-ve respectively, while albumin ranged from 1.31 to 1.53 g/dl in cont.+ve and cont.-ve respectively. Globulin level recorded the lowest value in T4 which was 5.15g/dl whereas the highest level in cont.-ve which was 16.67 g/dl. In conclusion, this investigation indicated that kaolin has reduced the toxicity effects of copper sulfate in common carp and the best level can be use was 6g/l (T3).